Laws compared and laborers colonial rights in Africa (1884-1910/1913). The ways of legal protection system on hiring contracts and their models (Congo Independent State, German colonies). Extreme law, extreme injury? - (:unkn) unknown (My University, 2015)
Sources and prospects: This conference comes from an unpublished colloquium organized by the French team CIRESC (International Research Center on Slaveries and Post-Slaveries) in 2015 at Bordeaux, France. We confront the models of economic exploitation and contract labour (indentured servants, engaged employees) in contemporary colonial Africa (late XIXth century), within two particularly controversial frameworks, both in their time and in current historiography. First, the Independent State of Congo / Congo Free State (Boma) under Leopold II, between 1884 and 1908, denounced for its atrocities and policy of "cut-off hands" in the exploitation of red rubber. The sovereign power was ultimately transferred to the Belgian State, following strong pressure exerted by the British; secondly, the German protectorates of Ausland (Schutzgebiete) from 1884 to 1916 (1918), lost with the end of the military model of the Reich under Kaiser Wilhelm II during the First World War in favour of the Allies : Deutsch-Ostafrika / Tanganjika Territorium, including Ruanda-Urundi (Daressalam), Deutsch-Südwesrafrika (Windhuk), Kamerun (Buea), the MusterKolonie of Togo (Lome), and their Hinterland. In the end, the long-term perspective is that of establishing a legal system inspired by Europe. At play are the logics of international law, borrowed from national cultures in a process of circulation and comparative law. A legal corpus is formulated on “workforce in colonies” for each public authority, published by International Colonial Institute at Brussels. Real melting pot of colonial law, agency is financed and promoted by ISC Companies, and his former Governor-general, Camille Janssen. Institution’s board Chairman is the duke Johann-Albrecht Herzog zu Mecklenburg, German Colonial Council member, President of The Deutsche Kolonialgesellschaft at Potsdam. He and his brother, as military personnel, were involved in colonial deportation operations in Africa. The Institute i
Keywords: African Research